Anatomy of torture - Hassner, Ron E. (Cornell University Press, 2022)
How Little We Know about Torture -- Three Myths about the Spanish Inquisition -- Learning to Torture : Ciudad Real (1484-1515) -- Correlates of Torture : Toledo (1575-1610) -- Exploratory Torture : Mexico City (1589-1591) -- Corroborative Torture : Mexico City (1594-1601) -- Lessons from the Spanish Inquisition -- Epilogue : The Ethics of Studying Torture.